Effect of Thermal Stage in the Processing Avocado by Flash Vacuum Expansion: Effect on the Antioxidant Capacity and the Qualitaty of the Mash. Issue 5 (15th September 2016) - Vargas‐Ortiz, Manuel; Servent, Adrien; Rodríguez‐Jimenes, Guadalupe; Pallet, Dominique; Salgado‐Cervantes, Marco
Abstract: The avocado presents a challenge in terms of industrialization, due to its high content of polyphenols and fats which are susceptible to oxidation processes. It contains enzymes that can cause various pulp deteriorations during agroindustrial processing, hence the need to add food preservatives in the traditional process. The flash vacuum‐expansion (FVE) process is usually used in the vinification to break down the tissues and free some compounds. This investigation conducted an FVE process kinetic study for avocado industrialization purposes, and evaluated its effect on lipoxygenase, antioxidant capacity, phenolic content and food quality properties of the mash. The couple temperature and time conditions attained during the kinetic study reduced the lipoxygenase activity by up to 70%, and the antioxidant capacity of the mashs obtained by FVE remained stable for 15 days without adding preservatives. The proportions in the food composition of the mash were consistent with those reported in the literature. Practical Applications: The results of our research suggest that the process of flash vaccum‐expansion, promotes extraction of bioactive compounds present in plant tissues that in traditional processes are considered as waste. The flash vaccum‐expansion process can be implemented for extracting pigments or to generate the disintegration of plant tissues or extractive fermentation pretreatments. So the products obtained in the process can serve as a basis for other processes or as a basis for various products. As shown in the results of our research, flash vaccum‐expansion process also allows the reduction of enzyme activity in plant products which increases the stability of the finished product, this consequently improves the nutritional quality, it promotes the availability of beneficial compounds and reduces oxidation processes.